Eficiência nutricional para fósforo e enxofre no abacaxizeiro ‘Pérola’ em Argissolo Vermelho-Amarelo - Andrade, Rayane Amaral de (2020)
Despite the amount of information related to mineral nutrition, little is known about the nutritional efficiency of pineapples. This work aimed to establish nutritional efficiency indexes for phosphorus (P) and sulfur (S) in the pineapple 'Pérola', depending on the application of nutrient doses. The experiment was carried out under rainfed conditions, between December 2014 and June 2016, in Argissolo Vermelho-Amarelo in the municipality of Itapororoca, in Paraíba State. The experimental design was a randomized blocks with three replications. The treatments were arranged in a modified experimental Plan Puebla III Matrix, and resulted from the combination of five doses of P (0.48; 2.8; 4.8; 6.7 and 9.1 g plant-1 P2O5) and five doses of S (0.48; 2.8; 4.8; 6.7 and 9.1 g plant-1). Seedlings of the type 'young' were used, planted in double rows, with no spacing of 0.80 × 0.40 × 0.40 m. In sampling performed after harvest, dry matter mass (ms), content (t) and accumulation (ac) of P and S in the root (rz), stem (ca), leaf (fo), seedling (mu), fruit (fru) and total (to). The nutritional efficiency of pineapple is assessed through the efficiencies of use (Efutz), conversion (Efcon), translocation (Eftra), absorption (Efabs) and recovery (Efrec). The doses of P and S increased the values of msfo, msmu, msfru and msto, but decreased those of msrz and msca. The levels of P and S in rz, ca and fru increased with those of specific nutrients, with antagonism between nutrients for tP and tS in leaves and seedlings. P doses increased acPrz, acPfo and acPto, while S doses increased acSfo and decreased acSmu and acSto, with synergism in acPfru, acSfru, acSrz and acSca, and antagonism in acPca. As doses of P and S increased as Efabs and Eftra (only P), but reduced the Efrec of the respective nutrients; there was synergism between the doses of P and S for Efutz (only P) and Efcon nutrients, and antagonism for EftraS. The EfrecP and EfrecS decreased with increasing doses, from 0.85 to 0.03 kg kg-1 and from 0.85 to 0.10 kg kg-1 with increasing doses from 0.48 to 9.1 g plant-1 of P2O5 and S, respectively. The recovery rates of the P and S media by the 'Perola' pineapple were 23.0 and 36.0%, respectively.